Collective bargaining in Northern Europe under strain: multiple drivers of change and differing responses to them - Dølvik, Jon Erik; Marginson, Paul (Oslo, 2018)
"Since the 1980s, wage regulation in Europe has been marked by decline and decentralization of collective bargaining. Since the turn of the century, this trend has been reinforced by increased mobility of labour and production factors in the wake of EU’s eastward enlargement, the economic crisis hitting especially southern Europe hard, and the deregulatory political intervention in labour markets instigated by EU and the Troika in these countries. How have these upheavals affected wage regulation in Northern Europe, which has been considered as the bedrock of coordinated collective bargaining and generally was less affected by the crisis?